Sosialisasi Penguatan Ekonomi Desa Melalui Literasi Digital Bagi Perangkat Desa Silo Baru - Wan Mariatul Kifti; Rohminatin; Amalia (STMIK Royal, 2026)
Abstract: Effective, transparent, and accountable village economic management is an important aspect in supporting rural development and community welfare. However, there are still limitations in the understanding of village officials regarding the use of information technology literacy in village economic management. This condition results in suboptimal management of economic data, activity documentation, and information dissemination to the community. This community service activity aims to enhance the understanding and awareness of Silo Baru Village officials regarding village economic management based on information technology literacy. The method used was community education through participatory socialization and counseling activities. The results indicate an improvement in the understanding of village officials regarding the importance of digital literacy as a supporting tool for planning, managing, and reporting village economic activities, as well as for promoting transparency and accountability in village economic governance. This activity provides an initial contribution to strengthening the capacity of village officials and supporting sustainable economic development in Silo Baru Village. Keywords: community service; digital literacy; economic management; village apparatus Abstrak: Pengelolaan ekonomi desa yang efektif, transparan, dan akuntabel merupakan aspek penting dalam mendukung pembangunan dan kesejahteraan masyarakat desa. Namun, masih terdapat permasalahan berupa keterbatasan pemahaman perangkat desa terhadap pemanfaatan literasi teknologi informasi dalam pengelolaan ekonomi desa. Kondisi ini berdampak pada belum optimalnya pengelolaan data ekonomi, dokumentasi kegiatan, serta penyampaian informasi kepada masyarakat. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman dan kesadaran perangkat Desa Silo Baru mengenai pengelolaan ekonomi desa berbasis literasi teknologi informasi. Metode yang digunakan adalah pendidikan masyarakat melalui kegiatan sosialisasi dan penyuluhan yang bersifat partisipatif. Hasil kegiatan menunjukkan adanya peningkatan pemahaman perangkat desa mengenai pentingnya literasi digital sebagai sarana pendukung perencanaan, pengelolaan, dan pelaporan ekonomi desa, serta sebagai upaya mendorong transparansi dan akuntabilitas tata kelola ekonomi desa. Kegiatan ini memberikan kontribusi awal dalam mendukung penguatan kapasitas perangkat desa dan mendorong pembangunan ekonomi Desa Silo Baru yang lebih tertib dan berkelanjutan. Kata kunci: ekonomi desa; literasi digital; pengelolaan ekonomi; perangkat desa